Hydrogen interaction on TM-decorated silicene - Narido, Shaira Jehsarine C. (Animo Repository, 2017)
First principles density functional theory calculations were performed to investigate the interaction of hydrogen molecules on Pt and Ni-decorated silicene. Results show that Ni-decorated silicene has higher initial hydrogen binding energy than Pt-decorated silicene, resulting to higher capacity for molecular hydrogen adsorption. The adsorption of hydrogen molecule for pristine metal-decorated silicene is via Kubas interaction, as evidenced by the hybridization of the hydrogen s states and metal adatom d states, electron poor regions around hydrogen molecule, and elongated bond length of hydrogen molecule (0.82-0.85Å). Succeeding hydrogen molecules are aligned towards the metal adatom, which suggests that interaction is physisorption via weak polarization along the hydrogen molecule axis.